A Review of Tetraploidy Induction Using Oryzalin in Various Plant Species: Morphological and Anatomical Implications - Velina Salsabil; Violita Violita; Annisa Putri Anggraini; Bella Nur Qamarani; Liza Febrianti; Nabila Sulaeman (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Polyploidy induction has emerged as a promising approach to improve plant traits through genetic and physiological modification. Oryzalin, a dinitroaniline herbicide, has been widelu recognized as an effective and less toxic alternative to colchicine for chromosome doubling in plants. This review aims to evaluate the effects of oryzalin-induced tetraploidy on the morphological, anatomical, and physiological characteristics of several plant species, including Colocasia esculenta, Citrullus lanatus, Tectona grandis, and Humulus lupulus. This study employed a narrative review with a systematic literatur search approach by collecting and analyzing previous studies related to the morphological and cytological responses of oryzalin treatments. The results indicate that oryzalin effectively induced tetraploidy, characterized by enlarged stomata size, reduced stomatal density, and altered leaf morphology, although species-specific responses were observed. The optimal oryzalin concentrations varied among species: 30 μM for C. esculenta, 72.2 μM for C. lanatus, 7.5 μM for T. grandis, and 10 μM for H. lupulus. In conclusion, oryzalin demonstrates strong potential as a safe and efficient mutagen for polyploid induction, supporting its application in plant breeding and genetic improvement. Further studies are required to optimize exposure duration and assess long-term physiological stability of induced polyploids.